2017
DOI: 10.1016/j.jtcvs.2017.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of stathmin 1 expression in patients with lung adenocarcinoma

Abstract: Stathmin 1 expression was an independent prognostic factor for adenocarcinoma, even when restricted to patients with early-stage cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Consistently, accumulating evidence has suggested that elevated STMN1 expression is closely correlated not only with the development and progression of cancer, 10,11 but also with poor survival. 16,26,[57][58][59][60] The evidence from a meta-analysis by Rong et al 16 confirmed that the overexpression of STMN1 was positively associated with high tumor stage, poor differentiation, and lymph node invasion. 10 However, to date, the prognostic value of STMN1 expression in solid tumors has not been systematically assessed by meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Consistently, accumulating evidence has suggested that elevated STMN1 expression is closely correlated not only with the development and progression of cancer, 10,11 but also with poor survival. 16,26,[57][58][59][60] The evidence from a meta-analysis by Rong et al 16 confirmed that the overexpression of STMN1 was positively associated with high tumor stage, poor differentiation, and lymph node invasion. 10 However, to date, the prognostic value of STMN1 expression in solid tumors has not been systematically assessed by meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Deparaffinization, rehydration, and antigen retrieval were performed by CC1 (prediluted; pH 8) antigen retrieval solution (reference 950-124; Ventana Medical Systems, Inc, Tucson, AZ), on a Ventana BenchMark-Ultra stainer (64 minutes at 100 C). Specimens were incubated with primary mouse anti-STMN1 antibody (OP18; dilution 1:200; Santa Cruz Biotechnology, Santa Cruz, CA; 32 minutes at 37 C) [6], then visualized with the OptiView DAB IHC and Amplification Kits (Ventana Medical Systems) for 12 minutes. The specimens were then counterstained with hematoxylin II and bluing reagent (Ventana Medical Systems) and placed on a coverslip.…”
Section: Ihc Stainingmentioning
confidence: 99%
“…STMN1 may thus be an attractive target for the diagnosis and treatment of malignant tumors [4,5]. We previously reported that STMN1 expression in lung adenocarcinoma (AD) and squamous cell carcinoma (SCC) was associated with vascular invasion, advanced tumor-node-metastasis stage, and shorter survival [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally identified in leukemia, where OP18 was found to be highly expressed [34,35]. In the past, OP18 has been studied most extensively in breast, gastric and lung cancer due to the high prevalence of these diseases [36][37][38][39][40][41][42].…”
Section: Functional Insights Into the Biological Role Of Op18 And Itsmentioning
confidence: 99%